Cohorting KPC+ Klebsiella pneumoniae (KPC-Kp)–positive patients: A genomic exposé of cross-colonization hazards in a long-term acute-care hospital (LTACH). (23rd October 2020) - Hawken, Shawn E.; Hayden, Mary K.; Lolans, Karen; Yelin, Rachel D.; Weinstein, Robert A.; Lin, Michael Y.; Snitkin, Evan S.
Abstract: Objective: Cohorting patients who are colonized or infected with multidrug-resistant organisms (MDROs) protects uncolonized patients from acquiring MDROs in healthcare settings. The potential for cross transmission within the cohort and the possibility of colonized patients acquiring secondary isolates with additional antibiotic resistance traits is often neglected. We searched for evidence of cross transmission of KPC+ Klebsiella pneumoniae (KPC-Kp) colonization among cohorted patients in a long-term acute-care hospital (LTACH), and we evaluated the impact of secondary acquisitions on resistance potential. Design: Genomic epidemiological investigation. Setting: A high-prevalence LTACH during a bundled intervention that included cohorting KPC-Kp–positive patients. Methods: Whole-genome sequencing (WGS) and location data were analyzed to identify potential cases of cross transmission between cohorted patients. Results: Secondary KPC-Kp isolates from 19 of 28 admission-positive patients were more closely related to another patient's isolate than to their own admission isolate. Of these 19 cases, 14 showed strong genomic evidence for cross transmission (<10 single nucleotide variants or SNVs), and most of these patients occupied shared cohort floors (12 patients) or rooms (4 patients) at the same time. Of the 14 patients with strong genomic evidence of acquisition, 12 acquired antibiotic resistance genes not found in their primary isolates. Conclusions: Acquisition of secondary KPC-Kp isolates carrying distinct antibiotic resistance genes was detected in nearly half of cohorted patients. These results highlight the importance of healthcare provider adherence to infection prevention protocols within cohort locations, and they indicate the need for future studies to assess whether multiple-strain acquisition increases risk of adverse patient outcomes.